Design and Implementation of SHMIOP Protocol for CORBA - Liu, Hongyi (International Journal of Computer Science and Information Technology, 2024)
CORBA as a distributed object middleware application standard of the object management organization, the use of GIOP protocol makes cross-platform client-server object communication possible, and the use of shared memory combined with the GIOP protocol can improve the efficiency of transmission. In this paper, we propose a design method for a shared memory-based communication protocol, SHMIOP protocol, and test and verify it on e*ORB middleware.